Crafting Interfaith Harmony through Ritual and Identity Integration: A Localised Muslim-Hindu Model from Saren, Bali, Indonesia - Supardi; Jauharudin (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2025)
Indonesia's complex religious landscape presents potential and persistent challenges in cultivating interfaith harmony, particularly in local contexts where theological divergence and structural segregation exacerbate communal divisions. This study examines the intentional construction of interreligious harmony in Saren Village, Bali, by analysing culturally embedded strategies employed by Muslim and Hindu communities. The research adopts a phenomenological approach, incorporating in-depth interviews, participant observation, and document analysis. It is theoretically grounded in Émile Durkheim's (1912) theory of social integration and Diana Eck's (2001) concept of religious pluralism. Durkheim highlights the role of shared rituals in generating collective solidarity and a cohesive moral order. At the same time, Eck emphasises active and equal participation across religious traditions as essential for a pluralist society. The findings demonstrate that traditional practices—such as Subak (a cooperative irrigation system), Bale Banjar (a local consensus forum), and Burdah (a Muslim devotional performance incorporated into Hindu ceremonial life)—serve as functional mechanisms for fostering interreligious cooperation, ritual synergy, and hybrid identity formation. Despite enduring challenges such as spatial segregation, cultural dominance, and digital polarisation, the Saren community sustains interfaith harmony through youth engagement, inclusive ritual adaptations, and grassroots digital literacy initiatives. Unlike many Balinese localities that reinforce Hindu cultural hegemony, Saren exemplifies a reciprocal model in which Muslim contributions, particularly the Burdah, are ritually embedded within dominant Hindu frameworks. This two-way assimilation of ritual practice marks a notable departure from conventional patterns of religious accommodation. Beyond applying Durkheim and Eck, this study contributes a contextual model of interfaith harmony grounded in reciprocal ritual integration. It underscores the value of local religious practices as generative sources for interreligious coexistence in plural societies.